AI in Education and Online Learning - Educational Leadership for Human-Centred Digital and Artificial Intelligence Transformation - Ardin Sianipar; Widya Angelina; Aldo Hutagalung (PAEDAGOGIA, 2026)
This study presents a systematic literature review (SLR) guided by the PRISMA 2020 protocol to synthesize the role of educational leadership in driving digital transformation and the adoption of artificial intelligence (AI) toward human-centered development in both traditional and open and distributed learning (ODL) environments. Drawing on 15 peer-reviewed studies (2018–2024), the findings reveal that leadership serves as a pivotal mediator between technological innovation and equitable educational outcomes. Three thematic pathways emerged: (1) leadership competence for AI integration, which determines institutional readiness and ethical governance; (2) human capacity building, where teacher digital literacy and pedagogical redesign translate technology into meaningful learning; and (3) ethical and inclusive AI practices that safeguard transparency, fairness, and accessibility. The study advances a Human-Centred AI Leadership Framework that integrates four domains—educational leadership, digital transformation, AI integration, and human development—within ODL ecosystems. Conceptually, it extends transformational and distributed leadership theories to socio-technical and ethical dimensions. In practice, it provides policy guidance for embedding AI governance, teacher professional development, and equity-driven digital strategies within national and institutional systems. The review highlights that the future of AI in education hinges not on automation but on leadership that combines technology with humanity.